Noragami : stray god. 6 - Adachi, Toka (Kodansha Comics, 2015)
While Kugaha continues to plot Bishamon's downfall, Yukiné wonders what happened to his new friend Suzuha. He sees Kazuma leaving flowers at Suzuha's cherry tree and follows him back to the heavens--right into the enemy stronghold. But when Bishamon attacks, Kazuma is forced to choose whose side he is really on.